“Projeto resgate do patrimônio histórico e cultural da UFRGS”: estudo do perfil dos incentivadores para o restauro do prédio da Faculdade de Direito - Oliveira, Dóris Maria Demingos (2017)
The Federal University of Rio Grande do Sul – UFRGS is a part of the history and memory of the State since 1895. Between the years 1996 to 1998, UFRGS executed an inventory, which concluded that its historical edifications were in decay due to time and use. In order to reverse this situation, the University looked for the Cultural Incentive law as a source for extra recourses, to face the restorations high costs, which it didn’t have in its own budget for the restoration of its cultural heritage. In 1999, through “Project Rescue of Historical and Cultural Patrimony of UFRGS” approved by MinC and, in 2000, was authorized a fund-raising through Law n. 8.313/91. Among its restored buildings, it’s the Faculty of Law´s building. The research presented sought to comprehend the reasons why people donated to the restoration of the Faculty of Law building. The employed methodology in this research was qualitative and made via in-depth interviewing, through which the profile of components and references was studied, considering the “cultural values” that motivated the promoters to donate. Concluding that the motivations for donations are memory and identity, reward and historical document, respectively in this order, followed by social means of interaction and ethics, as well as recognizing the importance that the restored place has on other people's lives.